Participation in Sport by Persons with Disabilities in Nigeria - Iyaluegbeghe, Clement Imonitie (Πανεπιστήμιο Πελοποννήσου, 2018)
This study titled Participation in Sport by Persons with Disabilities in Nigeria was aimed at (1.) identifying the challenges faced by athletes with disabilities in Nigeria, (2.) to investigate how to encourage participation in sport by persons with disabilities in Nigeria and (3.) to find out how to create awareness for the empowerment of persons with disabilities(PWDs) through sport. The qualitative method of study was adopted for the research project which involved the use of face-to-face interview to interface with the subjects of the study. Out of a population of 100, the convenient sampling method was used to select 25 subjects for the study, which included; 5 sport administrators, 5 coaches, 10 athletes with disabilities and 5 PWDs not involved in sport. The following results emerged: It was discovered that athletes with disabilities in Nigeria were faced with the following challenges; poor motivation, inadequate sport equipment for training, transport problem to and fro training ground, problem of poverty and lack, unemployment issue, poor funding of sport, lack of standard coaches/regular competitions, they are yet faced with the problem of access to public buildings, and non-recognition of athletes with disabilities. On how to encourage participation in sports by persons with disabilities in Nigeria the following fact were identified through the research survey: advocacy/awareness creation on the benefits of sports targeted at PWDs, scholarship/free education for PWDs which will expose them to PE and sports, attractive sport awards to athletes with disabilities/regular competitions to encourage PWDs to be involved in sports, provision of sport arenas where the people are, and incentive to PWDs who show interest in sport. On how to create awareness for the empowerment of PWDs in Nigeria the following points were brought to the fore: live demonstration of disability sports on TV, talks on the benefits of sport for PWDs on TV, Radio, and community centres, and demonstration of disability sport in community square. It is strongly believed that this study will contribute to the body of knowledge regarding disability sport and it will also contribute towards the development of sport for disabled persons in Nigeria and elsewhere.
Keywords: Physical education for people with disabilities - Nigeria; Sports - Health aspects; Sports for people with disabilities - Nigeria; Sports - Psychological aspects - Nigeria; Φυσική αγωγή για άτομα με ειδικές ανάγκες - Νιγηρία; Αθλητισμός - απόψεις υγείας; Αθλητισμός για άτομα με ειδικές ανάγκες - Νιγηρία; Αθλητισμός - Ψυχολογικές απόψεις - Νιγηρία; Empowerment; Disability sport; Advocacy; Awareness